Neurospora tetrasperma bibliography - Additions - David D. Perkins (Fungal Genetics Reports, 2003)
During the evolutionary divergence of N. tetrasperma from the eight-spored Neurospora species, ascus development was reprogrammed with the result that each of the four large ascospores is heterokaryotic, containing nuclei of both mating types, and germlings are self-fertile. Unique features of genome oganization, cell biology, and population structure have attracted investigators to use this pseudohomothallic, four-spored species for a wide range of studies. A bibliography listing 164 publications was published in 1994 in Fungal Genetics Newsletter 41:72-78. Eighty-six additional publications are listed here. In addition to recent papers, these include some theses, abstracts, and papers that were omitted from the previous list.